Malala's World: A Vivid Story in Context Conjunctural of the Cold PostWar - Agüero García, Javier (2017)
This work is an interpretive essay on the historical context in which Malala Yousafzai, the young Nobel Peace Prize laureate, lived in 2014. Through the conjunctural perspective, one begins with the Soviet invasion of Afghanistan, to recognize the origins of a conflict Which eventually involved Pakistan in a complex reality with the establishment of Afghan populations in a border region. It then explored Pakistani fundamentalism to provide a perspective of a phenomenon that flourished during the twentieth century, which began to become more important in the 1970s and has been more evident especially since 2001. Finally, Analyzes the lived history of Malala immersed in a fundamentalist environment commanded predominantly by the the Taliban.